The impact of metacognitive strategy use on Arabic text comprehension among secondary school students / Mohd Sham Kamis - Kamis, Mohd Sham (2021)
This thesis aimed to investigate the impact of utilizing the Metacognitive Strategy (MCS) in reading Arabic texts among students in Sekolah Menengah Kebangsaan Agama (SMKA) in Seremban, Negeri Sembilan. Specifically, this study was designed to; a) identify the use of planning, monitoring, and evaluating strategies in reading Arabic texts; b) identify the impact of MCS use on Arabic reading comprehension and vocabulary acquisition; and c) identify the problems in reading Arabic texts during the planning, monitoring, and evaluating strategies after receiving treatment. Generally, students who lack effective reading strategies might face difficulties in dealing with vocabulary and comprehension skills such as distinguishing different text structures and making inferences. Consequently, this may hinder students from mastering reading comprehension skills. In this study, the data were gathered using questionnaires, tests, and interviews. Specifically, 60 participants took part in answering the questionnaires, 30 participants for the tests, and six participants for the interviews. A mixed method design was applied to investigate the main variables. The analysis of data in the quantitative part that dominantly involved SPSS Version 26 was conducted to elicit information from the descriptive statistics and inferential statistics. In the qualitative part, thematic analysis was carried out based on the transcriptions gathered from the interviews. Data collected from descriptive statistics, inferential statistics, and thematic analysis were then triangulated to provide answers based on the three main objectives. The analysis of the data gathered revealed the following results. Firstly, the participants were found to be high users of the planning and monitoring strategies, while for the evaluating strategy, they were found to be moderate users. Secondly, the results showed a significant difference between the experimental group and the control group in the post-test score of the comprehension test and vocabulary test after controlling the extraneous variable. The results from the experimental group were higher than the control group because they former was exposed to the metacognitive strategies in the MCS Training as a treatment. Thirdly, the result showed that the participants faced a total of four problems in the planning strategy, two problems in the monitoring strategy, and two problems in the evaluating strategy. This study has theoretical and practical implications on classroom practice, specifically in the teaching and learning of the Arabic language. The findings demonstrated that MCS is an important factor to be considered when reading as this factor may affect the comprehension and vocabulary in reading Arabic texts. In addition, the findings showed that MCS training helped less successful learners to improve their comprehension and vocabulary learning in reading Arabic texts. The findings also suggested the importance of instilling awareness about metacognitive learning strategies among students and teaching metacognitive strategies explicitly through strategy trainings which can generate positive results among learners in reading comprehension.